Web-based horizon scanning: recent development with application to health technology assessment - Palomino, Marco A.; Taylor, Tim; Owen, Richard; McBridge, Geoff (Monitorowanie przestrzeni WWW: ocena nowych kierunków rozwoju technologii medycznych, 2012)
Horizon scanning is an increasingly important part of management decision-making. It involves the systematic search for incipient trends, opportunities and constraints that might affect the probability of achieving management goals and objectives. It requires the continuous acquisition of up-to-date information to anticipate issues and thus inform decisions. As an example of the application of horizon scanning in the public sector, the UK National Horizon Scanning Center provides policy-makers with forewarning about emerging and new health technologies. In this paper, we describe the implementation of a horizon scanning system centered on the use of keyword-based, Web search engines. By leveraging the existing infrastructure of proven search engines, our system aims to automate the human-intensive process of seeking information and emerging trends. A prototype implementation has been developed, and we discuss its potential in the context of a case study on proton beam therapy commissioned by the UK Department of Health
Informatyka Ekonomiczna = Business Informatics, 2012, Nr 3 (25), s. 139-159
Keywords: horizon scanning; Web data mining; strategic planning; information management; knowledge management; monitorowanie przestrzeni WWW; eksploracja danych w sieci Web; planowanie strategiczne; zarządzanie informacją; zarządzanie wiedzą